Demonstration of the Google Earth as a Tool in Learning the Earth Physics - Islami, Nur (Journal of Educational Sciences, 2018)
Earth Physics is a course at the Physics Education Program Study,University of Riau, Indonesia. The problem facing by students were thestudent commonly not able to imagine the rotation effect and the tilt ofrotation axis to some phenomenon. Furthermore the students were difficultto imagine the subduction zone of two tectonic plates. This study wasdemonstrate some assignments to the student regarding the use Google Earthin the learning the earth physically. In this study, a total of 38 students werechosen to use the Google Earth as an interactive learning media. Todemonstrate the Google Earth in the learning process, several assignmentshave been given to the students. The first was to compare the distancemeasurement manually and through Google Earth. The seconddemonstration was to define some selected areas. The third was todemonstrate the tilt axis of rotation effect on the earth. The last was a miniproject to demonstrate the use of Google Earth in imagine of the subductionof two tectonic plates. The result shows that mostly students (92%) wereable to reconstruction the process involved in the assignment although a fewof them cannot explain well. Whilst, 8% of the student were still difficult toreconstruction the process involved in the assignment, although they cansubmit all the assignments with fairly well. Finally, the Google Earth isgenerally success used in the demonstration of earth physics subject learningmedia.